Optimizing MSME marketing strategies through AI-based digital transformation: Towards smart and competitive MSMEs - Nisa Noor Wahid; Nijar Kurnia Romdoni; Ulfa Luthfia Nanda; Dwiyan Al Rasyid; Kurniawan Kurniawan (Universitas Pendidikan Indonesia, 2025)
Artificial Intelligence (AI)-based digital transformation has become an essential requirement for Micro, Small, and Medium Enterprises (MSMEs) to remain competitive in the digital economy era. Selasari Village, Pangandaran Regency, hosts two leading MSMEs, namely the Rajut Luwis knitting craft and the Crispy Pakis snack. Both enterprises previously relied on conventional marketing strategies, limiting their market reach. This community service program aims to strengthen MSMEs’ digital capacity through awareness sessions, training, and technical assistance in utilizing AI-based technology for product marketing strategies. The methods applied included socialization, practical sessions on AI-assisted digital content creation (product photography, automated editing, and promotional captions), as well as social media and marketplace management. The results indicate improvements in participants’ understanding and basic skills in using AI for digital promotion. Most participants were able to follow the workflow from product photography to editing and preparing ready-to-upload content, although some groups still required further mentoring. The optimization of MSME marketing strategies through AI utilization has proven to enhance operational efficiency, expand market reach, and create more personalized and relevant consumer experiences. This program serves as an initial step toward building a smart, adaptive, and competitive MSME ecosystem in Selasari Village within the digital economy era. Abstrak Transformasi digital berbasis kecerdasan buatan (AI) menjadi kebutuhan penting bagi UMKM supaya tetap kompetitif di era ekonomi digital. Desa Selasari, Kabupaten Pangandaran, memiliki dua UMKM unggulan yaitu kerajinan rajut Rajut Luwis dan camilan Crispy Pakis. Keduanya sebelumnya masih mengandalkan strategi pemasaran konvensional yang membatasi jangkauan pasar. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kapasitas digital UMKM melalui penyuluhan, pelatihan, dan pendampingan teknis pemanfaatan teknologi AI dalam strategi pemasaran produk. Metode yang diterapkan meliputi sosialisasi, praktik pembuatan konten digital berbasis AI (foto produk, pengeditan otomatis, dan pembuatan caption promosi), serta pengelolaan media sosial dan marketplace. Hasil kegiatan menunjukkan peningkatan pemahaman dan keterampilan dasar peserta dalam memanfaatkan AI untuk promosi digital. Sebagian besar peserta mampu mengikuti alur kerja dari pemotretan, pengeditan foto, hingga pembuatan konten siap unggah, meskipun masih terdapat kelompok yang membutuhkan pendampingan intensif. Optimalisasi strategi pemasaran UMKM melalui pemanfaatan AI terbukti meningkatkan efisiensi operasional, memperluas jangkauan pasar, serta menciptakan pengalaman yang lebih personal dan relevan bagi konsumen. Program ini menjadi langkah awal menuju ekosistem UMKM Desa Selasari yang cerdas, adaptif, dan kompetitif di era ekonomi digital. Kata Kunci: kecerdasan buatan; pemberdayaan desa; pemasaran produk; transformasi digital